The effects of extreme political acts and political risk on international banking systems. - Simpson, John (2007)
This study supports existing evidence of adverse domestic and international economic and financial spillover effects of extreme political acts. The relationship between the variables in the model is greater after the 9/11 event than before;the effects are greater in developed compared to developing banking systems: and the adverse effects had not dissipated in period of relative stability up to late 2004. In addition, USA political risk-adjusted banking returns together with world-banking system returns add new information in explaining country-banking system political risk-adjusted returns. This evidence should be heeded by risk managers and bank regulators in calculations of capital adequacy benchmarks to mitigate systemic flow-on effects.